Complementing the active surveillance criteria with multiparametric magnetic resonance imaging - Tae Un Kim; Seung Ryong Baek; Won Hoon Song; Jong Kil Nam; Hyun Jung Lee; Sung-Woo Park (Investigative and Clinical Urology, 2020)
Purpose: To evaluate the usefulness of multiparametric magnetic resonance imaging (mpMRI) to avoid misclassification of patients with clinically significant prostate cancer (PCa) into active surveillance (AS). Materials and Methods: Patients with Gleason grade group (GG) 1 PCa on systematic biopsy who underwent mpMRI before radical prostatectomy (RP) were included. mpMRI and pathologic results were compared between the AS and NOT-AS candidates. Unfavorable disease was defined as the identification of T3-4 disease or GG upgrade in the RP specimen. We established an ideal cutoff Prostate Imaging Reporting and Data System (PI-RADS) score for predicting unfavorable disease, and analyzed the location of index lesions on mpMRI. Results: PI-RADS scores were not significantly different between AS candidates (n=64) and NOT-AS candidates (n=136; p=0.629). Among 64 AS candidates, GG upgrading and unfavorable disease were diagnosed after RP in 24 (37.5%) and 25 (39.1%) patients, respectively. The rate of unfavorable disease was greater for patients with a PI-RADS score of 5 (83.3%) than in those with a score ≤4 (34.5%; p=0.030). Moreover, most PI-RADS 5 lesions in AS candidates were located in the anterior half of the prostate, with GG upgrading on targeted biopsy in 75.0% of cases. Conclusions: Among the patients with GG 1 PCa, PI-RADS scores did not differ significantly between AS and NOT-AS candidates. Nonetheless, AS candidates with PI-RADS 5 lesions were diagnosed with unfavorable disease in >80% of RP specimens. Significant cancer located in the anterior half of the prostate including the transitional zone can be missed by systematic biopsy.